El analfabetismo funcional docente, en el área de ciencias naturales y su incidencia en el desarrollo de las destrezas con criterio de desempeño, de los estudiantes de 4to a 7mo años de educación general básica, de la escuela Uruguay de la provincia de Loja, cantón Espíndola, parroquia Amaluza. Periodo lectivo 2012-2013 - Abad Abad, Flor María (2016)
This research called FUNCTIONAL ILLITERACY TEACHING IN THE AREA OF NATURAL SCIENCES AND THEIR IMPACT ON THE DEVELOPMENT OF SKILLS WITH PERFORMANCE CRITERIA OF STUDENTS GRADES 4th to 7th GENERAL EDUCATION BASIC SCHOOL "URUGUAY" THE Loja province, CANTON ESPINDOLA, PARISH Amaluza. School period 2012-2013". For which worked with the following objective determine the relationship between functional illiteracy in teaching and skill development with Performance Criteria in the area of Natural Sciences of children in 4th, 5th, 6th and 7th grades of basic general education; in which I helped to determine the functional literacy teaching and skill development with Performance Criteria in the area of Natural Sciences. The methodology used was the same that helped me to successfully develop this research, also the descriptive method, analytic-synthetic method, the inductive-deductive, statistical, scientific method, which used them when was used study and interpret the questions, instantly making the literature review, to organize information and I facilitated processes validity driveability of results and verification of hypotheses, also it allowed me to get the collection and bibliographic interpretation. We worked with 30 students and 4 teachers with which he could demonstrate and analyze the information obtained to verify the problems that exist in this institution. It is concluded that the development of skills with performance criteria, is essential to the teaching of natural sciences strategy, since by developing the skills the student contributes their own knowledge.